Effects of Attentional Withdrawal on Chinese Disabled Biathletes' Shooting Performance. (30th December 2021) - Li, Jin; Li, Sihua
Abstract : Under two situations of static empty gun preview and simulated competition, the validity of self-suggestion language "preloading compaction, " which suggests attentional withdrawal, was verified, respectively. Methods . The experiments in the two parts were designed in a single factor group. The participants (Chinese disabled biathletes) fired 20 times (4 groups in total, 5 times in each group) both in pretest and posttest, and they used self-suggestion before each group of firing in posttest. Optoelectronic shooting device based on wireless laser transceiver technology was selected to collect the shooting technical indicators, scores, and other information. The operation evaluation form reflected the subjective feelings of the participants, and the heart rate was measured by the chest band. Results . By the method of big data analysis, under the condition of static empty gun preview, the results showed that there was an extremely significant difference between shooting score and quality of triggering. All the marks on the operation evaluation form improved after the intervention. In the mock competition situation, shooting score has highly significant differences with quality of triggering and relative triggering value and significant difference with aiming ability. The marks of the operation evaluation form have been improved; the heart rate of firing all decreased in different degrees. Conclusions . The attentional withdrawal has positive effects on the shooting scores, technical indicators of optoelectronic shooting device, subjective feelings, and heart rate of disabled biathletes under the two conditions. TIRE (the timing of firing) is the most sensitive indicator and can be used as the focus of future training and scientific research.